A best way forward to the organisation of entomological training courses in sub-Saharan Africa - Jordaens, K.; Meyer, M. de; Nuffel, M. van; Kirk-Spriggs, A.H.; Sabuni, C.; Mwatawala, M.; Mujabwa, R.; Kabota, S.; Bellingan, T.; Goergen, G.; Mansell, M.; Manrakhan, A.; et al. (Elsevier, 2024)
Region, Diptera remain understudied. For a large part this is due to a lack of Diptera taxonomic experts and collection curators from the Afrotropical Region (except for South Africa perhaps), the difficulties some developing countries face in maintaining collections, and the low number of digitised specimens. This impedes the use of these Diptera collections for identification services, taxonomic and phylogenetic research, and other biological research areas. The dire need for knowledge transfer and training of young and emerging entomologists in the Afrotropical Region has prompted the Royal Museum for Central Africa and collaborating institutes to organise entomological training courses in the Afrotropical Region. The training courses take place in Africa, in strategic locations, cover a period of ten working days, are taught in English, and are free of cost to participants and lecturers. Here, we first provide a brief history of the evolution of the training courses. Second, we give a short description of the gender, age, educational and professional profile of the applicants and participants of the training courses. Third, we provide as much information as possible on all aspects of the organisation of the training courses. All information is freely available and documents are provided in Word or Excel format to facilitate future use by others. It is to be hoped that this information shall stimulate and facilitate the organisation of other entomological (or similar) training courses in the Afrotropical Region and other biogeographical regions. Such training courses will stimulate South-South networks for entomology research and the simultaneous training of participants with a different educational or professional background might foster collaborations between universities, other scientific institutes in postgraduate training and research. They may also initiate collaboration between scientific institutes and those involved in management, policy making, outreach, or implementation of legal procedures. We believe that this kind of training courses presents a best way forward in the organisation of similar capacity building activities that will contribute to a sustainable network of entomologists. Finally, these training courses may be one of the many possible ways to reduce the gender inequality gap in biological sciences in the Afrotropical Region.